2021
DOI: 10.34133/2021/8438614
|View full text |Cite
|
Sign up to set email alerts
|

Significant Reduction of Interfacial Thermal Resistance and Phonon Scattering in Graphene/Polyimide Thermally Conductive Composite Films for Thermal Management

Abstract: The developing flexible electronic equipment are greatly affected by the rapid accumulation of heat, which is urgent to be solved by thermally conductive polymer composite films. However, the interfacial thermal resistance (ITR) and the phonon scattering at the interfaces are the main bottlenecks limiting the rapid and efficient improvement of thermal conductivity coefficients (λ) of the polymer composite films. Moreover, few researches were focused on characterizing ITR and phonon scattering in thermally cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(53 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…The λ ∥ and EMI SE of the rGO/CNF composite films with 50 wt% rGO were 7.30 W (m K) −1 and 26.2 dB, respectively [ 20 ]. However, directly mixing the fillers and polymer has obvious disadvantages, which is difficult to form efficient fillers thermal conduction pathways and networks because the fillers are easily separated or coated by the polymer matrix [ 21 ]. Moreover, high interfacial thermal resistance between the fillers and polymer matrix results in low thermal conductivity for the prepared composites.…”
Section: Introductionmentioning
confidence: 99%
“…The λ ∥ and EMI SE of the rGO/CNF composite films with 50 wt% rGO were 7.30 W (m K) −1 and 26.2 dB, respectively [ 20 ]. However, directly mixing the fillers and polymer has obvious disadvantages, which is difficult to form efficient fillers thermal conduction pathways and networks because the fillers are easily separated or coated by the polymer matrix [ 21 ]. Moreover, high interfacial thermal resistance between the fillers and polymer matrix results in low thermal conductivity for the prepared composites.…”
Section: Introductionmentioning
confidence: 99%
“…Calculation based on the improved Hashin-Shtrikman model [18] showed that the surface functionalization of BNNS could effectively reduce the inplane and through-plane ITR F-M values from 0.1644 and 0.1696 to 0.1590 and 0.1587, respectively. In addition, Gu et al [19] prepared thermally conductive aminated reduced graphene oxide (NH 2 -rGO)/PI composite films. When the amount of NH 2 -rGO was 15 wt%, the λ ⊥ and λ ∥ of thermally conductive NH 2 -rGO/PI composite films reached 0.74 and 7.13 W m −1 K −1 , respectively, higher than pure PI film (λ ⊥ = 0.21 W m −1 K −1 , λ ∥ = 0.87 W m −1 K −1 ) and thermally conductive pristine rGO/PI composite films (λ ⊥ = 0.62 W m −1 K −1 , λ ∥ = 5.50 W m −1 K −1 ).…”
Section: Interfacial Thermal Resistance In Thermally Conductive Polymer Compositesmentioning
confidence: 99%
“…In addition, Gu et al . [ 19 ] prepared thermally conductive aminated reduced graphene oxide (NH 2 -rGO)/PI composite films. When the amount of NH 2 -rGO was 15 wt%, the λ ⊥ and λ ∥ of thermally conductive NH 2 -rGO/PI composite films reached 0.74 and 7.13 W m −1 K −1 , respectively, higher than pure PI film ( λ ⊥ = 0.21 W m −1 K −1 , λ ∥ = 0.87 W m −1 K −1 ) and thermally conductive pristine rGO/PI composite films ( λ ⊥ = 0.62 W m −1 K −1 , λ ∥ = 5.50 W m −1 K −1 ).…”
Section: Possible Directions For Breaking Through Bottlenecks For Thermally Conductive Polymer Compositesmentioning
confidence: 99%
“…On the other hand, GO, which can exhibit some functional properties 20–22 and improve the wettability of CF/EP to enhance the interfacial adhesion performance of the composite, is usually used to construct multiscale interfacial reinforced structure . 23–28 Zhang et al 15 used the sizing agent method to introduce GO at the interface region between CF and matrix.…”
Section: Introductionmentioning
confidence: 99%